Residue Management Impacts on Winter Canola in the Southern Great Plains. Issue 1 (1st June 2019) - Farrow, Blake; Sharma, Sumit; Jones, John W.; Lofton, Josh; Post, A.; Warren, Jason G.
Abstract : Core Ideas: Different wheat residue management strategies were evaluated for winter canola survival and yield. Plant stand declined during the course of growing season for all treatments. Plant stand and crown height data showed significant differences among treatments; however, the differences were inconsistent. This study showed that conservation tillage strategies did not significantly impact yield of winter canola. This study suggests that stand analysis data is not indicative of final yield data. The integration of winter canola in the southern Great Plains has allowed producers to diversify their cropping systems by offering an alternative winter crop. Canola is proven to be beneficial at managing grassy weeds and improving yields compared with continuous wheat systems. However, winter canola has been known to be susceptible to harsh winter conditions in the Southern Great Plains. The greatest losses in systems growing winter canola are generally caused by cold or freeze induced damage. The objective of this study was to evaluate impact of different residue management strategies on survival and yield of winter canola in the southern Great Plains. The management treatments included no‐till; vertical tillage at gang angle 0°, 3°, and 6°; harrowing; and prescribed burning. The effects of residue management strategies were evaluated by analyzing plant population, crown height, and yield during the growing season from 2014 to 2017 near Fairview, OK. Stand count was significantly different at different dates of measurement; however, the treatment differences were inconsistent. The burn treatment had significantly lower crown height than all treatments except no‐till in 2014. Vertical tillage gang angle 6° had significantly lower crown height than all treatments except the burn and harrow treatments in 2016. Canola yield combined across years showed no significant difference among the residue management treatments except for harrow, which showed significantly lower yield than rest of the treatments.